Socio Demographic Determinants and Co-Morbidities of Colorectal Cancer: Findings of a Case-Control Study (Bangladesh Armed Forces Medical Journal, 2025)
Introduction: Colorectal cancer (CRC), a multifactorial disease, is among the rapidly emerging illnesses in developing countries, associated with substantial morbidity and mortality. Diverse sociodemographic factors increase the risk of CRC.Objectives: To evaluate the sociodemographic factors associated with CRC.Materials and Methods: This hospital-based age and sex-matched case-control study involved 102 cases and 102 controls from the National Institute of Cancer Research and Hospital (NICRH) and Combined Military Hospital (CMH) in Dhaka between July 2020 and June 2021. Data was collected via semi-structured questionnaires and in-person interviews.Results: In this study, cases (mean age 44.7±13.9 years) and controls (mean age 45.6±13.3 years) comprised mainly females (56.9%). A higher proportion of cases resided in joint families (53.9% vs. 39.2%, p=0.035). Positive family history of CRC was noted in 5.9% of cases and 1.0% of controls (p=0.054). No significant difference was found between case and control group in case of education, occupation, marital status and income of the respondents(p>0.05). The prevalence of type 2 diabetes mellitus (T2DM) was considerably higher in patients (27.5%) compared to controls (15.7%, p=0.041). Dyslipidemia, H.pilori infection, Inflamatory bowel disease, Intestinal polyps were found more prevalent in cases than control which was statistically significant (p